MEDIA PEMBELAJARAN (Kajian terhadap Langkah-langkah Pemilihan Media dan Implementasinya dalam Pembelajaran) - Nunu Mahnun (An-Nida', 2012)
Learning media very urgent its existence in proeses teaching and learning, it contains that meaning media not only just as teacher complement for menyapaikan information to student in perform its teaching and learning activity at within class, but can become conditioner in ketercapaian usufructs to study that maximal. therefore task a teacher is how choose media in point in learning process in one’s line that will be reached it. To choose media in point in teaching and learning process required by teacher ability in understand media elect steps precisely and implementation in learning. Partly learns in choose media sometimes looked chanted, so bases experience sometimes looked just blackboard just that be made media in processes its learning, it who excites to work through media elect steps and its implementation.